The six : the untold story of America's first women astronauts - Grush, Loren (Scribner, 2023)
"When NASA sent astronauts to the moon in the 1960s and 1970s the agency excluded women from the corps, arguing that only military test pilots--a group then made up exclusively of men--had the right stuff. It was an era in which women were steered away from jobs in science and deemed unqualified for space flight. Eventually, though, NASA recognized its blunder and opened the application process to a wider array of hopefuls, regardless of race or gender. From a candidate pool of 8,000 six elite women were selected in 1978--Sally Ride, Judy Resnik, Anna Fisher, Kathy Sullivan, Shannon Lucid, and Rhea Seddon. In The Six, acclaimed journalist Loren Grush shows these brilliant and courageous women enduring claustrophobic--and sometimes deeply sexist--media attention, undergoing rigorous survival training, and preparing for years to take multi-million-dollar payloads into orbit. Together, the Six helped build the tools that made the space program run. One of the group, Judy Resnik, sacrificed her life when the Space Shuttle Challenger exploded at 46,000 feet. Everyone knows of Sally Ride's history-making first space ride, but each of the Six would make their mark" --